Contested understandings of recovery in mental health. (3rd September 2018) - McCabe, Rhiannah; Whittington, Richard; Cramond, Laura; Perkins, Elizabeth
Abstract: Background: The concept of recovery is contested throughout the existing literature and in mental health services. Little research exists that gives voice to service user perspectives of recovery. Aim: This paper explores how service users in two recovery oriented services run by the National Health Service in North West England talked about recovery and what it meant to them. Method: 14 service users accessing these services took part in semi-structured qualitative interviews focusing on the concept of recovery. Data were analysed using an interpretive phenomenological analysis approach. Results: Service users talked about recovery as a dynamic, day to day process as well as an outcome; specifically related to being discharged from inpatient settings. A number of factors including relationships and medication were cited to have the potential to make or break recovery. Conclusions: The study highlights the continued dominance of the biomedical model in mental health services. Service users appear to have internalised staff and services' understanding of recovery perhaps unsurprisingly given the power differential in these relationships. Implications for clinical practice are explored.